2019
DOI: 10.3365/kjmm.2019.57.12.778
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hot Stamping Heat Treatment Temperature on Resistance Spot Weldability of Al-10% Si Coated 30MnB5 Steel

Abstract: Hot stamping is the most efficient manufacturing process to produce high strength automotive parts with reduced springback. Recently, 30MnB5 steel has been developed for hot stamping steel which can provide above 1700 MPa. However, resistance spot weldability of this steel is insufficient due to the need for a large amount of carbon addition. In this study, the effect of the hot stamping heat treatment temperature on resistance spot weldability of Al-10% Si coated 30MnB5 was evaluated to improve the resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Regardless of the heating time, all three samples have martensitic structure, and as time increases, the martensitic lath size slightly increases. [18][19][20] It was found that the hot stamped samples consist of a compound layer, a diffusion layer, and a base metal; and as the heating temperature and heating time increase, the thicknesses of the compound layer and the diffusion layer increase.…”
Section: Microstructure Observation Of the Coating Layer (Alloy Layer)mentioning
confidence: 99%
See 1 more Smart Citation
“…Regardless of the heating time, all three samples have martensitic structure, and as time increases, the martensitic lath size slightly increases. [18][19][20] It was found that the hot stamped samples consist of a compound layer, a diffusion layer, and a base metal; and as the heating temperature and heating time increase, the thicknesses of the compound layer and the diffusion layer increase.…”
Section: Microstructure Observation Of the Coating Layer (Alloy Layer)mentioning
confidence: 99%
“…In general, when a steel sheet coated with a plating solution containing Al and Si is heat-treated at a high temperature of 850 °C or higher, compounds such as FeAl, Fe3Al, and Fe2Al5 are obtained. [18][19][20] However, the hot stamping of this study obtained compounds of Al5.4Fe structure and Fe2Si structure.…”
Section: Compound Of Coating Layermentioning
confidence: 99%